Effects of creative expression therapy for older adults with mild cognitive impairment at risk of Alzheimer’s disease: a randomized controlled clinical trial - Zhao J (Dove Medical Press, 2018)
Junyu Zhao,1 Hong Li,1,2 Rong Lin,1 Yuan Wei,1 Aiping Yang1 1School of Nursing, Fujian Medical University, Fuzhou 350108, People’s Republic of China; 2Department of Nursing, Fujian Provincial Hospital, Fuzhou 350001, People’s Republic of China Objective: Elderly people with mild cognitive impairment (MCI) are at high risk for dementia. This study compared the effects of standard cognitive training with a creative expression (CrExp) program. Methods: Adult patients with MCI aged 60 years and older (N=93) were randomly assigned to either CrExp therapy (n=48) or a control group who received standard cognitive training (n=45) for 16 weeks. The Montreal Cognitive Assessment, Chinese Version of the Auditory Verbal Learning Test, Chinese Version of the Category Verbal Fluency Test, Digit Span Test, Trail Making Test, Chinese Version of Activities of Daily Living scale, and Memory Satisfaction Questionnaire were used to measure cognitive functioning and daily living abilities. Assessments were administered at baseline, postintervention, and 6 months follow-up. Results: At postintervention, patients receiving CrExp therapy scored significantly higher than patients receiving standard cognitive training, in general cognitive functioning, memory, executive function, functional status, and everyday living ability. The improvements in cognitive functioning were maintained at the 6 month follow-up. Conclusion: CrExp therapy has greater positive effects on cognitive functions and daily living ability than standard cognitive training. This unique therapy may serve as a cost-effective adjunct to standard interventions for older adults with mild cognitive impairment. Keywords: cognitive impairment, creative expression, non-pharmaceutical therapy, health care